2016
DOI: 10.1051/pmed/2016026
|View full text |Cite
|
Sign up to set email alerts
|

Sélection des candidats en médecine : validité prédictive des mini entrevues multiples en contexte francophone

Abstract: -Contexte : Les mini entrevues multiples (MEM) sont un outil de sélection développé par une équipe de l'Université de McMaster pour évaluer les habiletés non-cognitives des candidats en médecine. La capacité des MEM à prédire les résultats aux études en médecine en contexte francophone reste à démontrer. But : L'objectif de cette étude est d'évaluer la validité prédictive des MEM en contexte francophone en utilisant les mini entrevues multiples francophones intégrées (MEMFI), développées conjointement par les … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Predictive validity was estimated by the association of interview and role‐play scores with average clerkship performance. A previous study showed that the IF‐MMI correlated better with clerkship performance than with the annual progress test and integrative courses used at this institution 34 …”
Section: Methodsmentioning
confidence: 80%
“…Predictive validity was estimated by the association of interview and role‐play scores with average clerkship performance. A previous study showed that the IF‐MMI correlated better with clerkship performance than with the annual progress test and integrative courses used at this institution 34 …”
Section: Methodsmentioning
confidence: 80%
“…A fairly consistent finding is that MMI scores are uncorrelated or inversely correlated to GPA or other measures of previous academic performance [11][12][13]. Positive associations were found between MMI scores and OSCE scores in medical school [12,[14][15][16], clerkship rotation evaluations [16][17][18], and in some contexts with exam scores [15]. Two multicenter studies have found correlations between MMI that were developed and implemented by institutions independently [10,19], suggesting some overlap between the constructs assessed in various settings.…”
Section: Introductionmentioning
confidence: 85%
“…In recent years, the IFMMI relied on a mix of discussion stations, role-plays and collaborative stations. It has already been found to show reliable scores [17,27] and some predictive validity with clerkship rotation performance [17,18]. Thus, the present study is part of a validation process which aims to appraise the dimensions that are evaluated by the IFMMI on the basis of their station format.…”
Section: Introductionmentioning
confidence: 97%
“…Data sources regarding Black people representation along the medical school admission continuum in Quebec, CanadaApplicants invited to Multiple Mini-Interviews (MMI) in 2019 and enrolled in a medical school All Quebec medical schools use an MMI in the second step of their selection process, where applicants go through a series of short interview stations in which they have to discuss topics with assessors, interact with actors, or accomplish a specific task 6. Université de Sherbrooke, Université Laval and Université de Montréal share the same interview, the Integrated French MMI (IFMMI),7 whereas McGill University has a different MMI.…”
mentioning
confidence: 99%